The cortisol awakening response—an exploration of intraindividual stability and negative responses - Carlsson Eek, Frida; Garde, Anne Helene; Hansen, Åse Marie; Persson, Roger; Ørbæk, Palle; Karlson, Björn (SJWEH Supplements, 2006)
' ' OBJECTIVES ': 'The purpose of the present analysis was to examine the prevalence and intraindividual stability of negative awakening responses in a healthy study population. Furthermore, it was of interest to elucidate the extent to which self-reported stress, sleep disturbances, or delay between awakening and the first salivary sample could explain the negative awakening response. ' ' METHODS ': 'Altogether 142 participants, 75 women and 67 men, were monitored during 3 workdays and 1 weekend day. On each day, the participants collected saliva at awakening, 30 minutes after awakening, 8 hours after awakening, and at 2100. ' ' RESULTS ': 'The daily prevalence of negative awakening responses varied between 19% on a workday and 38% on a day off. Altogether, 26% of the awakening responses were negative. Most of the participants had a mixture of positive and negative responses. The difference between positive and negative responses could not be explained by self-reported awakening time, subjective stress, or sleep disturbances. A delay between awakening and the first sample was more prevalent in cases of negative response, but it was also observed in cases of positive response. ' ' CONCLUSIONS ': 'Most people seem to exhibit one or more negative awakening responses occasionally. Essentially, therefore, the awakening response cannot be considered stable for one person. Although the negative awakening responses were not found to be clearly linked to self-reported awakening time, the actual time of awakening may influence the awakening response.
Keywords: awakening response; cortisol; cortisol awakening response; diurnal pattern; intraindividual stability; negative response; stability